Measurement invariance of the Cultural Intelligence Scale across three countries. (January 2022) - Brancu, Laura; Şahin, Faruk; Guðmundsdóttir, Svala; Çetin, Fatih
Abstract: The present study assessed the factor structure and measurement invariance of the Cultural Intelligence Scale (CQS) in university students from Romania, Turkey, and Iceland. A total of 730 undergraduates completed the 20 item-CQS. Confirmatory factor analyses indicated that the four-factor model, which consisted of metacognitive, cognitive, motivational, and behavioral dimensions, fit the data better than alternative models (three-factor and single-factor models). Discriminant and convergent validity of the CQS was also confirmed. Furthermore, the invariance of test for the CQS showed that the four-factor model of the CQS is suitable across three countries and the pattern of factor loading is invariant across these countries. However, the results did not support scalar invariance for three countries, which showed that partial measurement invariance was only established. In conclusion, the students in three countries reacted to the items for evaluating CQ in different ways, according to the findings of this study.